2022
DOI: 10.1002/advs.202105506
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Design of a Membrane‐Lytic Peptide‐Based Intravenous Nanotherapeutic Suppresses Triple‐Negative Breast Cancer

Abstract: Membrane-lytic peptides offer broad synthetic flexibilities and design potential to the arsenal of anticancer therapeutics, which can be limited by cytotoxicity to noncancerous cells and induction of drug resistance via stress-induced mutagenesis. Despite continued research efforts on membrane-perforating peptides for antimicrobial applications, success in anticancer peptide therapeutics remains elusive given the muted distinction between cancerous and normal cell membranes and the challenge of peptide degrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 121 publications
(135 reference statements)
1
22
0
Order By: Relevance
“…Unlike protein targets that can mutate and gain resistance against protein binding drugs, the tumor microenvironment and lipid compositions in the cell membranes are less likely to develop mutations and resistance and can be used as biomarkers for membrane‐active peptides. Multiple studies have shown the potential use of membrane‐active peptides to eradicate drug‐resistant cancer cells, cancer stem cells, and triple‐negative breast cancer (missing the common receptors in breast cancer), 47–50 whereas the gold standard doxorubicin (small molecules) and antibodies failed to treat them. In addition, our previous study found that cancer stem cells have difficulty gaining resistance against membrane‐active peptides over 28 days, whereas the cells developed drug resistance against doxorubicin in 10 days 50 .…”
Section: Development Of Membrane‐active Anticancer Peptidesmentioning
confidence: 99%
See 3 more Smart Citations
“…Unlike protein targets that can mutate and gain resistance against protein binding drugs, the tumor microenvironment and lipid compositions in the cell membranes are less likely to develop mutations and resistance and can be used as biomarkers for membrane‐active peptides. Multiple studies have shown the potential use of membrane‐active peptides to eradicate drug‐resistant cancer cells, cancer stem cells, and triple‐negative breast cancer (missing the common receptors in breast cancer), 47–50 whereas the gold standard doxorubicin (small molecules) and antibodies failed to treat them. In addition, our previous study found that cancer stem cells have difficulty gaining resistance against membrane‐active peptides over 28 days, whereas the cells developed drug resistance against doxorubicin in 10 days 50 .…”
Section: Development Of Membrane‐active Anticancer Peptidesmentioning
confidence: 99%
“…Multiple studies have shown the potential use of membrane‐active peptides to eradicate drug‐resistant cancer cells, cancer stem cells, and triple‐negative breast cancer (missing the common receptors in breast cancer), 47–50 whereas the gold standard doxorubicin (small molecules) and antibodies failed to treat them. In addition, our previous study found that cancer stem cells have difficulty gaining resistance against membrane‐active peptides over 28 days, whereas the cells developed drug resistance against doxorubicin in 10 days 50 . Several studies also showed that membrane‐active peptides can be utilized in combination cancer therapy to improve drug potency through enhancing membrane permeation and synergy 50–53 …”
Section: Development Of Membrane‐active Anticancer Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment of TNBC with natural medicines has also been investigated. Despite remarkable advances in the treatment of TNBC ( Chen et al, 2022 ), the lack of efficacious anticancer drugs is still a problem ( Zhang P. et al, 2022 ). In addition, the side effects of existing drugs are a major obstacle in the treatment of TNBC ( Olivier and Prasad, 2022 ; Zhang D. et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%